Inisiatif Digitalisasi Usaha Desa dan Dampaknya Bagi Sosial dan Ekonomi: Studi Kasus Pasardesa.id sebagai Mitigasi Ekonomi Panggungharjo Selama COVID-19 - Ameylia Puspita Rosa Dyah Ayu Arintyas; Raihan Chaerani Putri Budiman; Dhara Cita Rafeinia (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2023)
Villages are still stigmatized as backward areas, especially with digitization. Human resources are the main reasons villages cannot develop as massively as urban areas. Even though now the village is currently growing well. The COVID-19 pandemic is challenging for all regions. However, several studies show that the village is a survival area in the face of the COVID-19 pandemic. So it needs a reflection on how the village can have such a strong resilience that make it survive. This study aims to dig deeper into this matter. The case study was conducted in Panggungharjo Village, Bantul, D.I. Yogyakarta. This village is considered successful in working on clinical and non-clinical mitigation in handling COVID-19. This research focuses on economic mitigation through the Pasardesa.id platform as a form of village business digitization initiative to meet the needs of the village community. The method used is a case study qualitative method. As a result, Panggungharjo village has resilience values ​​such as trust cooperation which later became the basis for deals ​​to run this Pasardesa.id platform and were accepted by the community. In addition, several innovations result from the collaboration of actors, which foster various ideas and perspectives for the development of Pasardesa.id.